Molecular diagnosis of infectious diarrhea: focus on enteric protozoa. (November 2014) - Verkerke, Hans P; Sobuz, Shihab U; Petri Jr, William A
<x xml:space="preserve">Abstract</x> Robust detection of enteric protozoa is a critical step toward determining the etiology of diarrhea. Widespread use of conventional microscopy, culturing and antigen detection in both industrial and developing countries is limited by relatively low sensitivity and specificity. Refinements of these conventional approaches that reduce turnaround time and instrumentation have yielded strong alternatives for clinical and research use. However, advances in molecular diagnostics for protozoal, bacterial, viral and helminth infections offer significant advantages in studies seeking to understand pathogenesis, transmission and long-term consequences of infectious diarrhea. Quantitation of enteropathogen burden and highly multiplexed platforms for molecular detection dramatically improve predictive power in emerging models of diarrheal etiology, while eliminating the expense of multiple tests.